Shalawat Nariyah in the Perspective of Hadith: A Study of the Ma'ani Al-Hadith Approach - Firmansyah, Siddik; Rizki, Marisa (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2022)
Every Muslim who believes is encouraged to pray to the prophet known as tawassul (intermediary), shalawat nariyah contains praise and prayers to the prophet made by scholars without any teachings in the Hadith and the Koran. The purpose of this study is to see that shalawat nariyah is included in the recommendation of the Islamic religion as exemplified by the prophet or heresy?. The method of analysis used descriptive-comparative. The results showed that tawasul to the prophet and Allah's beloved creatures is allowed, while shalawat nariyah is a category of bid'ah Hashanah which is good because of the contents of shalawat nariyah are prayers and praises to the prophet. The hadith of the prophet showing praise and prayer to the prophet as an intermediary to get closer to Allah is highly recommended and sunnah practice it, with the intention of remaining Allah as a god who must be worshiped so as not to become shirk. The theoretical implications of this research provide a meeting point for shalawat nariyah in the hadith that relying on the prophet is recommended as long as it does not go outside the norms of Islam.